The integration of structural mechanics into microstructure solidification modelling. Issue 1 (May 2020) - Soar, P; Kao, A; Djambazov, G; Shevchenko, N; Eckert, S; Pericleous, K
Abstract: In situ structural mechanics are an often neglected area when modelling alloy microstructure during solidification, despite the existence of practical examples and studies which seem to indicate that the interaction between thermal or mechanical stresses and microstructure can have a significant impact on its evolution and hence the final properties at a macroscopic level. A bespoke structural mechanics solver using the finite volume method has been developed to solve the linear elasticity equations, with design choices being made to facilitate the coupling of this solver to run in situ with an existing solidification model. The accuracy of the structural mechanics solver is verified against an analytic solution and initial results from a fully coupled system are presented which demonstrate in a fundamental example that the interaction between structural mechanics and a solidifying dendrite can lead to a significant change in growth behaviour.